“Diseño de una máquina de lavado por inyección de piezas mecánicas”. - Lagla Lagla, Juan Carlos (2020)
The delay in the washing processes of the mechanical parts for the repair of automobile engines, limits production and economy in the local micro-industries. The present project referred to the study of the different washing processes of mechanical parts, in order to carry out the design of the machine for washing by injection in the microindustry "SERVIAUTOS", by means of the dimensions of the mechanical parts, the parameters were considered of machine design making use of the mechanical and fluid mechanics fundamentals. In addition, it was subjected to an evaluation in the structural and dynamic simulation of each of the present systems. The electrical process for driving the geared motor, the pump motor and the heating system was simulated using the CADE SIMU computational tool, while the mechanical and structural system under part standardization was performed using the AUTODESK INVENTOR software. The displacement that occurs in the structure, also with the tree and the rotary table when applying the maximum weight of 2493 N is 1.41 mm and the safety coefficient is 15 su, which allows to verify the rigidity of the machine for a possible implementation. The torque applied to the design is 60 Nm, which by means of the structural simulation, it is realized that the deformation reaches a maximum moment of 89,213 MPa. With this value, the materials do not deform as they have a resistance of 250 MPa.